An expert perspective on diversity-oriented standards for assessing sex and gender in clinical research - Hambruch, Hannah R.; Laskowski, Nora M.; Juster, Robert-Paul; Halbeisen, Georg; Paslakis, Georgios (Frontiers in Psychiatry, 2025)
IntroductionRandomized controlled trials require diverse patient groups to ensure broad applicability of results. However, gender minorities are often not included, which affects the generalizability and equity of healthcare outcomes. Inclusive research must consider the diversity of sex and gender to eliminate inequalities and improve health outcomes.MethodsA two-stage expert survey was conducted using a self-developed questionnaire in which the constructs of sex, gender, and gender expression were considered. Experts rated the importance and practicality of assessing these concepts in clinical trials and evaluated terms for suitability and comprehension. In addition, existing definitions were refined. Consensus was defined as 70% agreement or disagreement.Results14 out of 17 participating experts agreed on the importance to independently assess sex assigned at birth, and 9 out of 16 emphasized this for gender identity in clinical trials. Sex should be assessed with “Please specify your sex assigned at birth” and the answer categories “female”, “male”, “intersex”. Gender identity should be assessed with “I identify as…” and the answer categories “woman”, “man”, “nonbinary”, “trans woman”, “trans man”, “genderqueer”, “genderfluid”, “agender”, “two spirit”. Assessment of gender expression depends on the research question and may not be relevant for every study.DiscussionOur findings emphasize inclusivity by providing multiple gender options and improve data accuracy by allowing individuals to accurately report their gender identity. The results emphasize the importance of distinguishing between sex assigned at birth, gender identity, and gender expression in research. This ensures that gender diversity is accurately represented and considered, improving the relevance and inclusivity of clinical trials.